Strong and Electroweak Matter 2002: proceedings of the SEWM2002 meeting, Heidelberg, Germany, 2-5 October 2002 - Schmidt, Michael G. (World Scientific, 2003)
The SEWM2002 workshop, like the ones before, brought together theoretical physicists working on thermal field theory and, more generally, on (resummation) techniques for deriving effective actions based on QCD and the electroweak standard model of elementary particle physics, but describing nonstandard situations. The focus was on the temperature/chemical potential phase diagram of QCD, considered both analytically and with lattice gauge theory, equilibrium and nonequilibrium thermo field theory, and on heavy ion physics. Other related topics were "small x physics" in QCD, electroweak baryogenesis, inflation, and dark energy in the early universe